Development of Rural Tourism in China in the Context of Rural Revitalization - Yang, Lei (International Journal of Global Economics and Management, 2024)
Rural revitalization is an important development strategy in the new era of China, and rural tourism is a new industrial form that has flourished in recent years. As an important way to realize the strategy of rural revitalization, the impact of rural tourism on the countryside involves the rural economy, ecology, culture, governance and other levels, echoing the overall requirements of the country's five aspects of rural revitalization. At present, although the development of rural tourism in China has achieved certain results, there are still many deficiencies. Therefore, this paper first explores the role mechanism of rural tourism to promote rural revitalization, and then describes the current situation and problems of rural tourism development in the context of rural revitalization in China, and puts forward countermeasure proposals for rural tourism development on this basis.